Improving Undergraduate Students’ Argumentation Skills Through Problem-Based E-Module with Socio-Scientific Issues Topics - Anastasya Febrina Enggar Wati; Murni Sapta Sari; Suhadi Suhadi (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
E-module is considered as an effective learning media to create an interactive learning environment. In spite of that it is rare to find the research that examines the development of e-module based on Problem-Based Learning model that integrates Socio-Scientific Issues on argumentation skills to students. This research aims to develop students’ argumentation skills through problem-based e-module with socio-scientific issues topics. The researcher used pre-experimental method with one-group-pretest-posttest design. The e-module was implemented to 36 students of Biology Education, State University of Malang, for the 2nd-year from November to December 2022. The research sample was selected by non-random sampling. The research samples were selected by non-random sampling. The research data were collected by opened-ended questions to assess the students’ argumentation skills and categorized based on the argumentation skills rubric. The data were analyzed based on the increase of pre-test and post-test scores by using Normalized Gain (N-Gain). The result of the N-Gain calculation showed a score of 0.46 which means the students’ argumentation skills developed in the moderate category after the implementation of using problem-based e-module with socio-scientific issues topics. The problem-based e-module with socio-scientific issues topics can train students to identify the problems, analyze data and evidence to give problem-solving solutions packaged of complex argumentation.